PENERAPAN METODE STIMULASI MULTIMODAL PADA PASIEN GANGGUAN BAHASA AFASIA KONDUKSI PASCASTROK - Hidayah, Yurika Nur; Sheba, Shiane Hanako; Komaladini, Santi (JURNAL TERAS KESEHATAN, 2024)
Aphasia is a language disorder caused by damage to the brain areas responsible for language processing. Aphasia cases can be managed using multimodal stimulation methods. This study aims to apply therapeutic steps and determine the effectiveness of the multimodal stimulation method in improving sentence naming abilities in patients with post-stroke conduction aphasia. The method used is a case study with purposive sampling technique. Data collection was carried out after diagnosis and the determination of the appropriate therapy method, which involved conducting an initial test; providing multimodal stimulation therapy in 10 sessions, each lasting 45 minutes; and a final test. Data analysis was performed by comparing the results of the initial and final tests and calculating the percentage increase. The results show that the patient achieved a final percentage of 100% and a 9-point improvement, which falls into the successful category.